PENGARUH KOMBINASI KOMPOS DEKANTER SOLID DAN KONSENTRASI ASAM HUMAT CAIR TERHADAP PERTUMBUHAN BIBIT DUKU (Lansium domesticum Corr) - Rahmayani Siregar, Lili; Duaja, Made Deviani (Jurnal Agroecotania : Publikasi Nasional Ilmu Budidaya Pertanian, 2025)
This study aims to examine the effect of giving various combinations of solid decanter compost and liquid humic acid concentration, and to find the best dose combination for the growth of langsat seedlings. The study was conducted at the Teaching and Research Farm of the Faculty of Agriculture, University of Jambi, for 12 MST. The study used statistical analysis with a Randomized Block Design (RAK) pattern with 9 treatment and 3 replications. The results showed that the provision of a combination of solid decanter and liquid humic acid had a significant effect on the increase in plant height, root dry weight, crown dry weight and leaf chlorophyll, of langsat seedlings.